Assessing the Generalization of Relapse-Prevention Behaviors of Sexual Offenders Diagnosed With an Intellectual Disability. (January 2014) - Rea, Jerry A.; Dixon, Michael R.; Zettle, Robert D.
The generalization of relapse-prevention skills of 10 males residing at a state facility for sexual offenders diagnosed with an intellectual disability was assessed in the community using three different experimental probes: (a) treatment staff (TS), (b) nontreatment staff (NTS), and (c) community adults (CAs). Results indicated a decrease in compliance from the TS to NTS and CAs, with the lowest levels of generalization displayed by offenders who were older and displayed a wider range of paraphilias. The degree of generalization also varied as a function of the contingencies for prevention-plan noncompliance, with higher rates of generalization occurring for violations that were more severely consequated. The implications of the findings for future research in promoting the generalization of relapse-prevention skills of sexual offenders, in general, and those who also exhibit intellectual disabilities, in particular, are discussed.